Universalisme dan Misi Perspektif Kristen - Muhamad Ridwan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
Christian religion claims itself to be the universal religion, ie. the religion for all mankind. Therefore, evangelization or Christianization is the main part of Christian peoples and inseparable from their institution. But then that Christian universality encountered great challenge since the very beginning of the advent of Islam. The rivalry between both of them has been going on for 14 centuries.Various ways and means has been made by the Christians to subduing Islam and to proselytizing peoples, including in Indonesia that its majority of the peoples are Muslims. Muslims are difficult to be converted indeed, but most of them are unaware about what and how the tricky movements and the latent perils that imposed by the evangelization. Even if not being christianized, Muslims are secularized so they’re alienated from Islam and confrontational with their own religion. Yet, the idea about the universal religion is being misunderstood by the Christians. The truth is that the origin and the true “Christian” conceive the universal teachings, but confined to Jesus’ race only. Gospel—the holy scripture carried by Jesus—also prophesied the tidings about the coming of the universal religion in the future. But, Christian nowadays lost it real teachings. Besides, there’s so many verses, doctrines and teachings originated not from Jesus, one of  them is the command to proselytize peoples outside the Jews.